“We thought about it together and the solution came to our minds”: languaging linguistic problem-solving in multilingual Finnish classrooms - Repo Elisa; Kivimäki Riia; Kekki Niina; Alisaari Jenni (de Gruyter Mouton, 2022)
This study examines a learning experiment in which linguistic problem-solving tasks designed to increase students’ (aged 9–13) language awareness through collaborative dialogue were introduced in multilingual primary school classrooms in Finland. The aim was to analyse how the students (N= 126) reported what was happening during the linguistic problem-solving tasks, drawing on the method of languaging. Additionally, the study investigates how meaningful, relevant and novel the students with diverse backgrounds found the tasks. The data were collected via a survey. Students’problem-solving reports were analysed via content analysis, with the Taxonomy of Cognitive Process applied. Statistical analysis was used to measure the experienced meaningfulness, relevance and novelty. The analysis resulted in an understanding of the multiple voices in which the students articulated their thinking regarding linguistic problem-solving. The study sheds light on how to develop language aware learning materials to engage all students, regardless of their backgrounds, in discussions on language.